CASE REPORT: EXOGENOUS CUSHING SYNDROME IN A GROWING CHILD FOLLOWING CHRONIC TOPICAL STEROIDS FOR FAMILIAL PSORIASIS - Tan, Tsae Yun (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Cushing syndrome is relatively uncommon in young children but exogenous Cushing syndrome is increasingly seen due to both prescribed and surreptitious intake of steroids. CASE We report a 6 year-10-month-old female, referred from Dermatology for obesity. She had itchy and scaly red plaques about 1 year prior. Both her mother and elder sister had been diagnosed with psoriasis and treated elsewhere. Even without a doctor’s advice, she was given over-thecounter topical betamethasone dipropionate by her mother 1 year before consult. The mother applied the steroid generously over the child’s whole body including the face and inguinal region twice a day for every flare, which usually occurred around 2 episodes every month. Since then, her daughter gained weight and stopped growing. She had florid Cushingoid features with emotional lability (easily tearing), truncal obesity, thick violaceous purple striae over the trunk, neck, upper, and lower limbs, and extensive erythematous scaly psoriatic plaques (BSA 80%). She was hypertensive with blood pressures ranging from 130-150/88-100 mmHg. She did not have proximal muscle weakness. Her eye assessment was negative for glaucoma or cataract, or hypertensive retinopathy changes. She had a pre-pubertal Tanner stage with no virilisation or hirsutism. She had persistently suppressed 8am cortisol level (<27.6 nmol/L) and low ACTH level (1.10 pmol/L, reference range 1.6-13.9) with normal 17OHP and DHEAS screen. She had borderline HbA1c (5.7%), dyslipidaemia, and non-alcoholic fatty liver disease based on an abdominal ultrasound. Her topical steroids for psoriasis were stepped down and she was initiated on steroid-sparing UV phototherapy in the ward. Her BP stabilized. She was given physiologic oral hydrocortisone replacement (6 mg/m2/day). Six months later, her weight reduced with resumption of linear growth, and improved metabolic control. CONCLUSION Exogenous Cushing syndrome resulting from topical medications has been described well especially among young infants. Potent topical steroids particularly for young children should ideally be administered with doctor’s prescription.